Stapled peptides: targeting protein-protein interactions in drug development - Qian Zhang; Ziyang Wang; Xiaohan Mei; Quan Chen; Chunqiu Zhang (Exploration of Drug Science)
Protein-protein interactions (PPIs) impersonate a significant role in many biological processes and are potential therapeutic targets in numerous human diseases. Stapled peptides, as the most promising therapeutic candidate for interfering with PPIs, have a higher degree of α-helicity, improved binding affinity, more resistance to proteolytic digestion, longer serum half-life, and enhanced cell permeability, which exhibits higher pharmacological activity compared with small molecule drugs and biologics. This review outlined the continuous progress of stapled peptides mainly concerning the design principle, structural stability, bioactivity, cell permeability, and potential applications in therapeutics, which is aimed at providing a broad reference for the design and exploration of stapled peptides with enhanced biological and pharmacokinetic properties as the next-generation therapeutic peptide drugs targeting various diseases.